O35 Efficacy & safety of tocilizumab in GCA: a multi-centre experience of NHS clinical practice. (20th April 2020) - Sebastian, Alwin; Kayani, Abdul; Ranasinghe, Chavini; Hall, Frances; Ransom, Colin; Jayne, David; Quick, Vanessa; Hughes, Mark; Stack, John; Mukhtyar, Chetan; Coath, Fiona; Bharadwaj, Anurag; et al.
Abstract: Background: Giant cell arteritis (GCA) has a relapsing, remitting course with ischemic/vascular damage in a number of cases. Glucocorticoids (GC) remain mainstay of treatment with SAEs e.g. diabetes and fractures commonly seen. The GiACTA trial of tocilizumab (TCZ) in GCA led to NICE approval for 12 month's therapy in relapsing/ refractory disease. We report real life experience in 51 cases. Methods: Multicentre retrospective data collected through ENRAD and individual centres across England (Table 1). Outcomes were as assessed by supervising clinicians. Results: Fifty-one patients were treated with TCZ (26 cranial, 13 LVV, 11 both). 11 (22.0%) had prior permanent sight loss due to AION, CRAO or both. One died prior to TCZ, from recurrent cerebral infarcts. Mean age was 71 years with 66.7% females. Ultrasound (US) was used for diagnosis in 28 (56.0%), exclusively or in combination with other tests such as biopsy, PET-CT or CTA. 70% had prior DMARD (LEF/MTX/AZT/MMF/CYC, mean duration 58 weeks). MTX was used in 50% alone or combination. Initial TCZ was given as subcutaneous or intravenous (85.4% and 14.6%). TCZ indication in 89.8% was relapsing, refractory or ischemic disease. Steroid AEs that prevented optimal GC dosing constituted 10% of TCZ indication. Mean follow up was 31 weeks, 30 (58.8%) continuing TCZ uninterrupted, 4 completed 12 months, 4 discontinued due to SAEs. Ten had brief interruptions due to minor AEs. One restarted after 12 months due to flare but died 12 weeks later from abdominal aortic aneurysm rupture. At follow up, 37(74%) were in remission with a mean GC dose of 6.97 mg (mean GC dose pre-TCZ 33.2 mg), Thirty-two (65.3%) ≤ 5mg. In 4 (8%) outcome could not be assessed as either they started TCZ recently or about to start. In 53% lipids were not checked after commencing TCZ. AEs seen were 37.0%. Conclusion: In clinical practice, TCZ is efficacious and safe in relapsing/refractory/ischemic GCA. I.V. route is an option awaiting NHSE approval in refractory visual symptoms. Infections and other AEs do occur but overall safety profile is acceptable. US is excellent in identifying patients at need and is a useful disease activity monitoring tool. Disclosures: A. Sebastian: None. A. Kayani: None. C. Ranasinghe: None. F. Hall: Consultancies; Sobi, S. Grants/research support; Actelion. C. Ransom: None. D. Jayne: None. V. Quick: Honoraria; Roche. M. Hughes: None. J. Stack: Member of speakers' bureau; Roche. C. Mukhtyar: None. F. Coath: None. A. Bharadwaj: None. V. Hajela: None. S. Butler: Consultancies; Lily. M. Lwin: None. C. Edwards: Consultancies; Roche, Chugai. Grants/research support; Roche, Chugai. M. Whitlock: None. B. Dasgupta: Consultancies; Roche, Sanofi, GSK. Grants/research support; Roche.